The longitudinal relationship between motor competence and measures of fatness and fitness from childhood into adolescence - Rodrigo Antunes Lima; Anna Bugge; Annette K. Ersbøll; David F. Stodden; Lars B. Andersen (Elsevier, 2019)
Objectives: To examine longitudinal (seven years) relationships among cardiorespiratory fitness (VO2peak), body fatness, and motor competence. Method: Data were collected as part of the Copenhagen School Child Intervention Study (CoSCIS). Body fatness was assessed by the sum of four skinfolds. VO2peak was measured directly in a continuous running protocol. Motor competence was assessed using the Körperkoordinationtest für Kinder. This study used multilevel linear mixed models to evaluate the reciprocal longitudinal association between body fatness, VO2peak, and motor competence. All regressions were stratified by sex and adjusted by intervention and pubertal status. All variable coefficients were standardized. Results: A reciprocal relationship was observed between children's motor competence with body fatness and VO2peak at the seven-year follow-up (6-13 years of age). Children with higher motor competence at baseline had a lower risk of having higher body fatness (βboys = −0.45, 95% CI: −0.52 to −0.38; βgirls = −0.35, 95% CI: −0.42 to −0.28) and higher VO2peak (βboys = 0.34, 95% CI: 0.27-0.40; βgirls = 0.27, 95% CI: 0.20-0.33) during childhood. Alternatively, higher body fatness or lower levels of VO2peak at baseline were associated with lower motor competence during childhood. Conclusions: These data suggest motor competence, body fatness, and VO2peak demonstrate reciprocal relationships across childhood (6-13 years of age). Interventions addressing motor competence, cardiorespiratory fitness, and body fatness in early childhood are recommended, as intervention effects are likely to be enhanced because of the mutual reciprocal associations between these three variables. Resumo: Objetivos: Examinar as relações longitudinais (sete anos) entre a aptidão cardiorrespiratória (VO2 pico), gordura corporal e coordenação motora. Método: Os dados foram coletados como parte do Copenhagen School Child Intervention Study (CoSCIS). A gordura corporal foi avaliada pela soma de quatro dobras cutâneas. O VO2 pico foi medido diretamente em um protocolo de corrida contínua. A coordenação motora foi avaliada com o teste de coordenação corporal para crianças (Körperkoordination für Kinder - KTK). Usamos modelos lineares mistos multiníveis para avaliar a associação longitudinal recíproca entre a gordura corporal, o VO2 pico e a coordenação motora. Todas as regressões foram estratificadas por sexo e ajustadas para intervenção e estado puberal. Todos os coeficientes das variáveis foram padronizados. Resultados: Observamos uma relação recíproca entre a coordenação motora e a gordura corporal. As crianças com maior coordenação motora no início do estudo apresentaram menor risco de ter maior nível de gordura corporal (βmeninos = -0,45, IC de 95%: -0,52: -0,38; βmeninas = -0,35, IC de 95%: -0,42: -0,28) e maior VO2 pico (βmeninos = 0,34, IC de 95%: 0,27: 0,40; βmeninas = 0,27, IC de 95%: 0,20: 0,33). Por outro lado, maior nível de gordura corporal ou menores níveis de VO2 pico no início do estudo foram associados a menor coordenação motora durante a infância. Conclusões: Esses dados sugerem que a coordenação motora, gordura corporal e VO2 pico demonstram relações recíprocas durante a infância (6-13 anos). São recomendadas intervenções que abordem a coordenação motora, a aptidão cardiorrespiratória e a gordura corporal na primeira infância, pois os efeitos da intervenção são provavelmente maiores devido às associações recíprocas mútuas entre essas três variáveis. Keywords: Motor development, Longitudinal studies, Health behavior, Risk factors, Obesity, Physical fitness, Palavras-chave: Desenvolvimento motor, Estudos longitudinais, Comportamento saudável, Fatores de risco, Obesidade, Aptidão física